Fungicide sensitivity levels in the Lithuanian Zymoseptoria tritici population in 2021 - Lavrukaitė, Karolina; Heick, Thies M.; Ramanauskienė, Jūratė; Armonienė, Rita; Ronis, Antanas (Frontiers in Plant Science, 2023)
Zymoseptoria tritici causes winter wheat disease septoria leaf blotch and is a major factor in yield losses worldwide. Farmers are led to use fungicides to protect their crops; however, the efficacy of these measures is rapidly decreasing due to natural mechanisms of mutation emergence in pathogen populations. Fungicide resistance is being recorded worldwide; therefore, screening of the existing situation in Lithuania is essential to determine further steps for crop protection strategies. In this study, in vitro fungicide sensitivity tests, mutation detection, and field experiments were carried out. The mean EC50 values for prothioconazole-desthio and mefentrifluconazole were 0.14 and 0.28 mg/l, respectively. The increase in the frequency of the mutation S524T highly related to DMIs resistance was observed. The dominant point mutation in gene CYP51 was I381V, and the most frequent CYP51 haplotype was D13 (V136C, I381V, Y461H, S524T). The mutation G143A related to QoI resistance was detected in ¾ of the population. Mutations conferring resistance to SDHIs were not detected in single pycnidia isolates. Two year field experiments also showed no decline in field efficacy of SDHI fungicide in Lithuania. Moreover, the baseline sensitivity of the Lithuanian Z. tritici population to QiI fungicide fenpicoxamid was established. The findings of this study show further development of the fungicide resistance in the Lithuanian Z. tritici population.